Experimental comparison of a matrix converter using Si IGBT and SiC MOSFETs - Trentin, Andrew; De Lillo, Liliana; Empringham, Lee; Wheeler, Patrick; Clare, Jon C. (IEEE, 2015)
This paper presents an analytical and experimental comparison between comparable Silicon (Si) IGBTs and Silicon Carbide (SiC) MOSFETS when used in a direct AC/AC matrix converter circuit. The switching performance of the two devices is analysed and the efficiency / losses measured in order to develop a loss model which will help engineers to design and develop matrix converter circuits using these types of devices. Particular attention is given in the paper to the discrepancies found between the data-sheet values and the measured data. The EMI performance of the two matrix converters is also determined and the implication of using high speed devices from both an EMI and an efficiency point of view is formulated together with an improved input filter design.